Efficacy of Acetaminophen Plus Amitriptyline Compared to Acetaminophen to Reduce Pain Intensity in Nonspecific Chronic Lower Back Pain - Nita Kurniawati1, Isti Suharjanti2, Muhammad Hamdan2, Joseph Ekowahono Rahardjo2, Djohan Ardiansyah2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: There was 90% of Lower back pain (LBP) are non-specific. Acetaminophen is the first an analgesic in the treatment of LBP, but some cases of chronic LBP need additional antidepressant drugs. Amitriptyline is an antidepressant drug often used in cases of pain, but the evidence research in the case of non-specific chronic LBP is still a contradiction. Method: The study was a Double-Blind Randomized Controlled Trial using consecutive sampling admissions. The subjects were divided into 2 groups; acetaminophen plus amitriptyline group and acetaminophen plus placebo group. Results: There was no significant difference in pain intensity of acetaminophen plus amitriptyline and acetaminophen plus placebo groups either statistically or clinically (p = 0.498; OR = 0.667; CI 95% 0.20-2.16; ARR = -0.07 or -7%). The significant improvement of pain intensity in the treatment group Acetaminophen plus Amitriptyline was 24 (72.7%), while in the control group Acetaminophen plus Placebo was 24 (80.0%). In the treatment group was 9 (27.3%) who did not experience a significant improvement in pain intensity, and in the control group was 6 (20.0%). Conclusion: There was no difference in efficacy between acetaminophen plus amitriptyline with acetaminophen plus placebo to reduce pain intensity in non-specific chronic LBP